PRESPEKTIF PERKEMBANGAN TEORI MANAJEMEN SUMBER DAYA MANUSIA (HRM) DALAM STRATEGI SUMBER DAYA MANUSIA (SHRM) BERBASIS RBV - Ratnawati Dwi Putranti Honorata (Serat Acitya, 2013)
Human Resource Mangement (HRM) in the process of trying to join a management strategy in this field of study has generated a lot of conceptions and practitioners of the articles on certain HR practices proposed to be associated with a variety of corporate strategy. Plus more research to examine the factors on HR practices from a strategic perspective. Through the development of new disciplines related to Human Resource Mangement Strategy (SHRM). The reason for this theory is still in the growth of the suggestions and criticisms are very significant is needed in this field of study. Resource-based view suggests that human resource systems can contribute to sustainable competitive advantage through facilitating the development of firm-specific competencies, produce complex social relationships, which is embedded in the history and culture of the company, and generate knowledge organization In this paper we provide an overview of the development of the theory of HR (Human Resources) in the development of human resource strategies based RBV. In HRM research should be based on organizational context, HRM issues is part of an open system, and the research that theoretically would be detrimental if it is not placed in the broader organizational context. In a change both in terms of operation, system and structure of the company because the business environment is dynamic and therefore difficult to dipridiksi.Namun SDM is a vital competitive advantage for the management of other resources that depend on human resources management.